(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
In implementing trade policy measures, governments usually select from a range of instruments including quotas, subsidies (explicit or implicit) and tariffs. In this paper we consider the potential gain of a government pursuing a two-part trade policy: an import license for entry, along with a per-unit tariff on imports. The model is a three-step game between home and foreign countries in the Cournot duopoly. The paper demonstrates that two-part trade policy is dominant.